An insight into internship program for undergraduate Arabic language learners in Malaysia - Sahrir, Muhammad Sabri; Ismail, Taufik; Shamsul Tajri, Saiful Adli (Faculty of Education, University of Malaya, 2016)
This study attempts to investigate the outcome of the internship training program in the Department of Arabic Language and Literature, at the International Islamic University Malaysia (IIUM). Methodologically, this study was conducted to gather the opinions and experience on the internship program among Arabic language and literature students. The participants were purposively selected from 57 out of 66 students who have completed their three months internship program either in the public or private sector from July to September 2015 by using an online survey and open-ended questionnaire. General findings from this study show that internship training has essentially improved their soft skills and increased their workplace literacy and well-being. Despite the poor perception of Arabic language in the mutual graduate employability as well as its practicality aspects and job market by the industry, Arabic language and literature students are well accepted in both private and public sectors to undertake their internship training as reported in this article. In conclusion, internship training is crucial, particularly among Arabic language and literature students as it enriches their experiences, knowledge and skills in both their personal and social life. It also increased their level of confidence to explore their future opportunity in the Malaysian job market including setting up their own businesses through entrepreneurship knowledge and skill